2020
DOI: 10.3847/2041-8213/ab930a
|View full text |Cite
|
Sign up to set email alerts
|

A Data-driven Technique Using Millisecond Transients to Measure the Milky Way Halo

Abstract: We introduce a new technique to constrain the line-of-sight integrated electron density of our Galactic halo DM MW,halo through analysis of the observed dispersion measure distributions of pulsars DM pulsar and fast radio bursts (FRBs) DM FRB. We model these distributions, correcting for the Galactic interstellar medium, with kernel density estimationwell-suited to the small data regime-to find lower/upper bounds to the corrected DM pulsar /DM FRB distributions: »   max DM 7 2 stat 9 sys pc cm pulsar 3 Unifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…The mass and ionisation state of this (baryonic) halo component has been estimated in a number of ways, but remains poorly constrained. Methods include studies of (1) of the cold and hot components on the Galactic halo using high velocity clouds [113] and column densities of ionised metals (such as Silicon), (2) DM measurements to pulsars in the Magellanic Clouds [182], (3) the diffuse X-ray emission around the Milky Way [183] and (4) the ionised halos formed around galaxies in cosmological simulations [108]. The DMs of pulsars in the Large Magellanic Cloud imply DM halo > 15 pc cm −3 .…”
Section: Probing the Milky Way Ism And Ionised Halo Using Frbsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass and ionisation state of this (baryonic) halo component has been estimated in a number of ways, but remains poorly constrained. Methods include studies of (1) of the cold and hot components on the Galactic halo using high velocity clouds [113] and column densities of ionised metals (such as Silicon), (2) DM measurements to pulsars in the Magellanic Clouds [182], (3) the diffuse X-ray emission around the Milky Way [183] and (4) the ionised halos formed around galaxies in cosmological simulations [108]. The DMs of pulsars in the Large Magellanic Cloud imply DM halo > 15 pc cm −3 .…”
Section: Probing the Milky Way Ism And Ionised Halo Using Frbsmentioning
confidence: 99%
“…Constraining the halo's mass density and ionisation through DM measurements of nearby FRBs has been proposed by Platts et al [182], among others. They used pulsars and a small number of nearby FRBs to obtain a conservative upper limit on DM MW,halo of 123 pc cm −3 (95% confidence), and estimate that several thousand FRBs are required to significantly improve constraints on DM MW,halo .…”
Section: Probing the Milky Way Ism And Ionised Halo Using Frbsmentioning
confidence: 99%
“…Platts, Prochaska, & Law (2020) have made a similar analysis using the DMs of Galactic pulsars combined with the DMs of published FRBs, introducing a kernel density estimation technique to find lower and upper bounds for . They place a constraint of (95% confidence interval), assuming a spherical distribution of the baryons.…”
Section: Galactic Electron Density Modelsmentioning
confidence: 99%
“…They place a constraint of (95% confidence interval), assuming a spherical distribution of the baryons. Tighter constraints may be derived using the Platts et al (2020) framework as the sample of FRBs grows, and in particular as more low-DM (i.e. nearby) FRBs are found.…”
Section: Galactic Electron Density Modelsmentioning
confidence: 99%
“…Such a sample is not available yet. However, Platts et al (2020) recently demonstrated a new method of inferring the MW CGM contribution to the DM of FRBs. Applying it to existing measurements they report min[DM tot ] = 63 +27 −21 ± 9 pc cm −3 , where the first error is statistical and the second -systematic.…”
Section: Model Parameter Spacementioning
confidence: 99%